The effect of gibberellin, temperature, and length of the seed storage period of different species of Nepeta on germination characteristics - Parvin Salehi; Hamideh Javadi; Leila Rasoulzadeh; Leila Falah Hoseini (علوم و فناوری بذر ایران, 2024)
In this study, the effect of short-term storage conditions in one season on the characteristics of seed germination of 3 species of Nepeta was studied. A factorial experiment was conducted. Treatments included 1) Storage period (in five levels 0, 1, 2, 3 and 4 months), 2) storage temperature (at three levels of the laboratory environment, cold storage +4 and -18 °C), and 3) germination treatment (at two levels of control and gibberellin 250 ppm). The results showed that the germination characteristics of different species are different at the time of harvest, So that at the time of harvesting, N. glomerulosa with 29% showed lower germination compared to two species, N. haussknechtii and N. pogonosperma, with 87 and 89% germination. Storage for 3 to 4 months increased the germination percentage of N. glomerulosa about 53% and N. haussknechtii and N. pogonosperma about 10%. It can be concluded that N. glomerulosa has primary dormancy, and by keeping it for four months, the post-harvesting demands of this species are released. While the species N. haussknechtii and N. pogonosperma did not have primary dormancy. The study of seed storage at +25, +4 and -18 °C showed that the best temperature for short-term seed storage, until the next cropping season, for N. glomerulosa subsp. Staffina is temperature +4 °C and for N. haussknechtii and N. pogonosperma is -18 °C. The germination behavior of N. haussknechtii and N. pogonosperma are very similar and is completely different from N. glomerulosa subsp. Staffina.